Hak Memperoleh Keadilan Dalam Sistem Peradilan Di Indonesia - Aniek Perian; Rusito (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2022)
Constitutionally, the Indonesian state has guaranteed, respected, respected and protected human rights. Beforethe amendments were made, the 1945 Constitution could be said to have not explicitly stated the guarantee ofhuman rights. However, after the amendment of the 1945 Constitution, especially the second amendment in2000, the provisions regarding human rights in the 1945 Constitution have undergone fundamental changes.This amendment to the 1945 Constitution contains human rights material as regulated in Article 28Aparagraph (1) to Article 28j paragraph (2). By using normative juridical research methods, this study aims todetermine the efforts that must be made to obtain justice in the justice system in Indonesia. The justice to beenforced in the constitutional state of the Republic of Indonesia is justice that contains the values of thePancasila philosophy, the 1945 Constitution and the values contained in other legislation, whose values areaspirational with the values and sense of community justice. Meanwhile, the way to enforce law and justice iscarried out in accordance with the implementation procedure based on the principle of presumption ofinnocence and other principles determined by the Criminal Procedure Code.